Answer:
The ratio is multiplying 1.6 so just pick all the proportional relationships where you have to multiply by 1.6.
Step-by-step explanation:
Proportional relationships man you have to multiply, but since I didn't know what you multiplied 5 to get to 8 I divided.
8÷5=1.6
And if you want to check your answer then multiply.
5×1.6=8
<u><em>Could I please have BRAINLIEST?</em></u>
Assuming you mean the central angle, semicircles have central angles of
.
Answer:
Option C
Step-by-step explanation:
complete question
A. 35[3]6cB. 12[3]12cC. 12[3]6cD.72c
The given equation can be written as
5^3√6c+7^3√6c
5 *
+ 7 * ![\sqrt{3 *3*2c}](https://tex.z-dn.net/?f=%5Csqrt%7B3%20%2A3%2A2c%7D)
5 * 3 *
+ 7 * 3 *![\sqrt{2c}](https://tex.z-dn.net/?f=%5Csqrt%7B2c%7D)
15 *
+ 21 *![\sqrt{2c}](https://tex.z-dn.net/?f=%5Csqrt%7B2c%7D)
36 *![\sqrt{2c}](https://tex.z-dn.net/?f=%5Csqrt%7B2c%7D)
12 [3]*![\sqrt{2c}](https://tex.z-dn.net/?f=%5Csqrt%7B2c%7D)
Option C is correct
Answer:
D
Step-by-step explanation:
Factor x^2+2x-8
(x-2)(x+4) = 0
Solve for x
x = 2
x = -4
Answer:
Step-by-step explanation:
Equation
3x + 9 + 2x = x - 2x - 3
Solution
Combine all the like terms.
3x+2x+9 = x - 2x - 3
5x + 9 = -x - 3 Add x to both sides of the equation
5x+x +9 = -x+x -3 Combine
6x + 9 = - 3 Subtract 9 from both sides of the equation
6x+9-9 = - 3-9 Combine
6x = -12 Divide both sides by 6
6x/6 = -12/6
x = - 2
Answer x = - 2